2020
DOI: 10.3390/toxins12070424
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Ochratoxin A Content in Grape Pomace by Different Methods

Abstract: Grape pomace (GP) is the residue of grapes after wine making and is a valuable source of dietary polyphenol and fiber for health promotion. However, studies found the presence of ochratoxin A (OTA) in GP at very high concentrations, which raises a safety issue in the value-added utilization of GP. This study evaluated the effects of thermal pressure, baking, acid and enzymatic treatments on OTA content in GP. Thermal pressure treatment was conducted with wet GP at 121 °C for 10–30 min in an autoclave; acid tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Ochratoxin A is a very persistent mycotoxin and is not considered to be reduced during wine aging. Several studies have dealt with its reduction throughout the winemaking process using solid mass adsorption and fermentation or by an additional laborious process [35,36]. Terminating any processes before storing, OTA is stable in an acidic medium.…”
Section: Discussionmentioning
confidence: 99%
“…Ochratoxin A is a very persistent mycotoxin and is not considered to be reduced during wine aging. Several studies have dealt with its reduction throughout the winemaking process using solid mass adsorption and fermentation or by an additional laborious process [35,36]. Terminating any processes before storing, OTA is stable in an acidic medium.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [ 114 ] determined the effect of enzymatic processing on the fate of OTA in grape pomace or OTA in buffer solution. When OTA buffer solution (pH 5.4) was treated with flavozyme, lipase, and carboxypeptidase A at 37 °C for 24 h, 36, 60, and 100% of OTA reduction was observed, respectively, while these enzymes reduced 10.2% (lipase) and 18.3% (carboxypeptidase A) of OTA in grape pomace, and flavozyme did not reduce any OTA [ 114 ]. They also showed that this difference was due to the polyphenols in grape pomace that can inhibit different hydrolytic enzymes such as proteaseand lipase [ 114 ].…”
Section: Effects Of Food Processingmentioning
confidence: 99%
“…When OTA buffer solution (pH 5.4) was treated with flavozyme, lipase, and carboxypeptidase A at 37 °C for 24 h, 36, 60, and 100% of OTA reduction was observed, respectively, while these enzymes reduced 10.2% (lipase) and 18.3% (carboxypeptidase A) of OTA in grape pomace, and flavozyme did not reduce any OTA [ 114 ]. They also showed that this difference was due to the polyphenols in grape pomace that can inhibit different hydrolytic enzymes such as proteaseand lipase [ 114 ].…”
Section: Effects Of Food Processingmentioning
confidence: 99%
See 2 more Smart Citations